Terapi Relaksasi untuk Menurunkan Tekanan Darah dan Meningkatkan Kualitas Hidup Penderita Hipertensi - Sulistyarini, Indahria (Faculty of Psychology, Universitas Gadjah Mada, 2013)
The aim of this study was to investigate the effect of relaxation training on blood presure and quality of life among patients with hypertension. The hypothesis of this study is stated that there is an influence of relaxation training to blood presure and quality of life among patients with hypertention. The quality of life was measured by using quality of life scale based on aspect from WHOQOL (1998). An experimental method used was a pre-posttest control group design. The data was analyzed by using anava mixed design and an independent samples of t-test was followed by analysis of covariance to test the difference of mean sistolic and diastolic blood pressure between treatment groups both experiment and control group. The calculations and analysis were performed by using SPSS 17.0 for windows. The results indicate a significant decrease of sistolic blood pressure (t=–9,213, p